If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + -3y = 0 Solving 2a + -3y = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '3y' to each side of the equation. 2a + -3y + 3y = 0 + 3y Combine like terms: -3y + 3y = 0 2a + 0 = 0 + 3y 2a = 0 + 3y Remove the zero: 2a = 3y Divide each side by '2'. a = 1.5y Simplifying a = 1.5y
| 2(a-5)=-2 | | 4d-7=21 | | 10y=3zx+1 | | a=5i-3j+3k | | F(x)=-x^3+12x+4 | | 5ln(x^2)=0 | | (6x)^5/(3x) | | (6x)^5/(12x) | | 1+x^20=0.5 | | 5z+8=3z+16 | | 5(p+2)-(p+4)=3p-1 | | 3m+3=15-m | | 50/0.15 | | -4(y-2)=-8 | | 4(a+2)=-4 | | 12x+9x=15 | | .25(3x+12)+2x=-5(.25x+3) | | 2sin(2x-10)=1.2516 | | 2u-20=14 | | y=xp^2+p^2 | | 5x+132=6x-21+7x-1 | | (x+3)(x-9)(6-x)=0 | | x^2-x-1+3i=0 | | 3x+(2-4x)=4 | | 8/21k=1/3 | | y-aw=2w-1 | | 5-x/6=2x/3 | | -6y=-3x+18 | | X-3/5=2x/8 | | 4x/3=2/9 | | -9y+9x=18 | | 3x+5+2+4=19 |